Transcriptional quiescence in primordial germ cells. (2nd November 2018) - Lebedeva, Lyubov A.; Yakovlev, Konstantin V.; Kozlov, Eugene N.; Schedl, Paul; Deshpande, Girish; Shidlovskii, Yulii V.
Abstract: In most animal species, newly formed primordial germ cells (PGCs) acquire the special characteristics that distinguish them from the surrounding somatic cells. Proper fate specification of the PGCs is coupled with transcriptional quiescence, whether they are segregated by determinative or inductive mechanisms. Inappropriate differentiation of PGCs into somatic cells is thought to be prevented due to repression of RNA polymerase (Pol) II-dependent transcription. In the case of a determinative mode of PGC formation ( Drosophila, Caenorhabditis elegans, etc.), there is a broad downregulation of Pol II activity. By contrast, PGCs display only gene-specific repression in organisms that rely on inductive signaling-based mechanism (e.g., mice). In addition to the global block of Pol II activity in PGCs, gene expression can be suppressed in other ways, such as chromatin remodeling and Piwi-mediated RNAi. Here, we discuss the mechanisms responsible for the transcriptionally silent state of PGCs in common experimental animals, such as Drosophila, C. elegans, Danio rerio, Xenopus, and mouse. While a PGC-specific downregulation of transcription is a common feature among these organisms, the diverse nature of underlying mechanisms suggests that this functional trait likely evolved independently on several instances. We discuss the possible biological relevance of these silencing mechanisms vis-a-vis fate determination of PGCs.